The Health Care Cost of Elder Abuse: An Analysis of Medicare, Medicaid, and Adult Protective Services Data in Maine, 2006-2014 - Ziller, Erika C. ([Verlag nicht ermittelbar], 2024)
In partnership with the Maine Department of Health and Human Services, this study analyzed approximately 200 case files of Maine Adult Protective Services (APS) substantiated investigations of financial exploitation that were opened and completed from 2007 through 2012. The case files included detailed information about the types of abuse individuals experienced, their functional limitations, and severity of risk status. The research team linked the case files with the individuals' Medicare and Medicaid claims data from 2006 through 2014 to examine their claims experience one year prior to APS contact, during their APS event year, and two years following their APS event year. Using a quasi-experimental design, the research team established health care use and cost profiles of the APS clients and compared their profiles to matched controls in the general older population. The project aimed to advance knowledge of the financial impact of elder abuse.